Mapping of suitable release areas for the parasitoid Dolichogenidea gelechiidivoris (Marsh) for the classical biocontrol of Tuta absoluta (Meyrick) using temperature-dependent phenology models - Mujica, N.; Carhuapoma, Pablo; Kroschel, Jürgen; Kreuze, Jan F. (2024)
The South American tomato leafminer, Tuta absoluta (Meyrick) is a major invasive pest of tomato (Lycopersicum esculentum Mill.) worldwide. Among the different integrated pest management strategies, biological control is most promising. Dolichogenidea gelechiidivoris (Marsh) is a larval endoparasitoid native to the Neotropics, where it is the dominant biological agent of T. absoluta along the Peruvian coast. The determination of the parasitoid’s temperature-dependent development is crucial for better predicting the potential of the parasitoid to establish in new regions and to control the target pest. Therefore, the effect of temperature on the development and reproduction of D. gelechiidivoris was studied at five constant temperatures ranging from 10 to 30°C in its main host T. absoluta. The Insect Life Cycle Modeling (ILCYM) software was used to fit nonlinear equations to collected life table data and to establish an overall phenology model to simulate life table parameters based on temperature. The parasitoid completed its life cycle at constant temperatures from 15 to 30°C; the temperature of 10°C was lethal to pupae. The theoretical lower threshold temperatures for the development of egg-larvae and pupae were 7.6°C and 10.9°C respectively. The egg-larval and pupae stages had the lowest mortality between the temperature range of 20-30°C. The lowest senescence rates for females and males were observed within the temperature range of 10–20°C. Oviposition time decreased significantly with increasing temperature from 16.7 days (10°C) to 1.6 days (35°C). Mean fecundity was highest at 20°C (74.4 eggs/female). Maximum population growth is expected around 24.3°C with a finite rate of increase, λ of 1.1088, which corresponds to a population doubling time of 6.7 days. The highest values for gross reproduction rate (GRR) and net reproduction rate (R0) were found between 20 and 21°C, and the shortest mean generation time (T) was observed at 30°C (19.9 d). Suitable release areas with a very high probability of establishment and potentially good control efficacy of the parasitoid are tropical and subtropical regions (e.g., countries in Southern Europe; Spain, Portugal). The potential use of the parasitoid in the context of classical biological control of T. absoluta is discussed.